Photocatalytic co-production of hydrogen and alkanes from short chain fatty acids over Cu2O particle: Effects of electron donors. (14th December 2017) - Zheng, Xian-Jun; Zhao, Meng; Li, Cui-Ling; Zheng, Zhi; Wei, Li-Fang; Chen, Feng-Hua; Wang, Huan-Xin; Chen, Ping-Ping; Qin, Xiao-Mei
Abstract: Effects of electron donors on photocatalytic production of H2 and hydrocarbons over Cu2 O photocatalyst have been systematically investigated in this paper. The cubic Cu2 O has been synthesized by reduction precipitation method and further characterized by XRD, SEM and UV–vis DRS. Short chain fatty acids (SCFAs) including acetic acids, propionic acids and butyric acids, main by-products produced during dark H2 fermentation, have been chosen as typical electron donors. Experimental results showed that distributions of gaseous products during photocatalytic water-splitting process were greatly influenced by individual and mixed SCFAs. Using three mixed SCFAs as electron donors, the overall carbon recoveries obtained in this study are in range of 86.11–95.36%. The AQEs in our photocatalytic system are changed from 4.88% to 8.94%. The AECEs in our photocatalytic system are varied from 4.46% to 10.48%. Based on our experimental results, a novel route for renewable energy generation from organic wastes or wastewater can be established by coupling dark H2 fermentation with photocatalytic system. According to distributions of gaseous products and known intermediates, a possible mechanism about photocatalytic decomposition of SCFAs for production of H2 and hydrocarbons has been proposed and analyzed as well. Highlights: Using individual SCFAs and mixed SCFAs as electron donors in photocatalytic system. Effects of individual and mixed SCFAs on distributions of gaseous products. A systematic report about co-production of alkanes and H2 from individual and mixed SCFAs. Photocatalytic degradation mechanism of individual and mixed SCFAs for production of alkanes and H2 .